Cedera Kepala Sedang setelah Kecelakaan Lalu Lintas (KLL) Tunggal : Sebuah Laporan Kasus - Putri, Intan Utami; Putri , Pratiwi Hendro; Agiestya, Milla Monica; Fa’dlillah, Dwi Noor; Paranggai, Elhi Andi; Windiyani, Firly (Medula, 2024)
According to the Brain Injury Association of America, a head injury is damage to the head, not congenital or degenerative, but caused by an external physical attack or impact, which can reduce or change consciousness which can cause damage to cognitive abilities and physical function. Traffic accidents are the main cause of head trauma or head injuries. A 23 year old man came to the emergency room at Jendral Ahmad Yani Metro Hospital accompanied by his family with complaints of a single post-KLL headache in the Pekalongan area, East Lampung on August 20 2023, because he hit a monument and fell from a motorbike without wearing a helmet. History of fainting for 30 minutes, vomiting without spraying 3x after waking up. Complaints accompanied by difficulty opening the left eye, swelling and pain. On physical examination, vulnus excoriation, vulnuslaceratum and vulnuscontussum were found. The diagnosis of moderate head injury (CKS) accompanied by secondary injury and sinistra oculi hematoma can be confirmed by history taking, physical examination, neurological examination, and supporting examinations in the form of laboratory examinations, CT scans and MRI. Management in this case includes primary survey, secondary survey, observation of general condition and vital signs. The patient received further treatment in the Neurology ward for 3 days.